2010
DOI: 10.1074/mcp.m110.001263
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteomics Analysis Reveals a Role for E2F2 in the Regulation of the Ahr Pathway in T Lymphocytes

Abstract: E2F transcription factors (E2F1-8) are best known for their role in cell proliferation, although it is clear that they regulate many other biological processes through the transcriptional modulation of distinct target genes. However, the specific set of genes regulated by each E2F remains to be characterized. To gain insight into the molecular pathways regulated by E2F2, we have analyzed the proteome of antigen receptor-activated T cells lacking E2F2. We report that loss of E2F2 results in a deregulated Aryl-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…These results suggest that E2F2 modulates cellular sensitivity to xenobiotic signals through the negative regulation of the AHR pathway. Remarkably, a comparison of proteome and transcriptome profiling results derived from the same cellular systems has shown a clear discrepancy in individual targets regulated by E2Fs (Azkargorta et al 2006;Azkargorta et al 2010;Infante et al 2008;Li et al 2006a;Liontos et al 2009;Muller et al 2001). These discrepancies may be explained by the different methods of assay/sample preparation, different detection sensitivity, alternative splicing, posttranscriptional regulation, PTMs, selective degradation of proteins, and the time discrepancy between mRNA and protein expression.…”
Section: Protein Profiling To Elucidate E2f Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that E2F2 modulates cellular sensitivity to xenobiotic signals through the negative regulation of the AHR pathway. Remarkably, a comparison of proteome and transcriptome profiling results derived from the same cellular systems has shown a clear discrepancy in individual targets regulated by E2Fs (Azkargorta et al 2006;Azkargorta et al 2010;Infante et al 2008;Li et al 2006a;Liontos et al 2009;Muller et al 2001). These discrepancies may be explained by the different methods of assay/sample preparation, different detection sensitivity, alternative splicing, posttranscriptional regulation, PTMs, selective degradation of proteins, and the time discrepancy between mRNA and protein expression.…”
Section: Protein Profiling To Elucidate E2f Functionmentioning
confidence: 99%
“…Interestingly, comparative proteomics has also revealed novel pathways regulated by E2F2. We have recently found that mediators of the Aryl-hydrocarbon receptor (AHR) are aberrantly expressed in the proteome of proliferating E2F2 -/-lymphocytes relative to wild-type counterparts (Azkargorta et al 2010). Consequently, E2F2…”
Section: Protein Profiling To Elucidate E2f Functionmentioning
confidence: 99%
“…Liquid chromatography-tandem MS (LC-MS/ MS) spectra were acquired using a Q-TOF micro mass spectrometer (Waters, Milford, MA) interfaced with a CapLC System (Waters) as previously described (20). Briefly, each sample was loaded onto a Symmetry 300 C18 NanoEase Trap precolumn (Waters) connected to a XBridge BEH130 C18, 75 m ϫ 150 mm, 3.5 m (Waters).…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin Immunoprecipitation Assay-Chromatin immunoprecipitation (ChIP) assay was performed as previously described (20). Briefly, mouse T cells stimulated with anti-CD3 were crosslinked using formaldehyde and lysed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation